Siblings Promote a Type 1/Type 17‐oriented immune response in the airways of asymptomatic neonates. Issue 6 (26th February 2016) - Wolsk, H. M.; Chawes, B. L.; Følsgaard, N. V.; Rasmussen, M. A.; Brix, S.; Bisgaard, H.
Abstract: Background: Siblings have been shown to reduce the risk of childhood asthma and allergy, but the mechanism driving this association is unknown. The objective was to study whether siblings affect the airway immune response in healthy neonates, which could represent an underlying immune modulatory pathway. Methods: We measured 20 immune mediators related to the Type 1, Type 2, Type 17, or regulatory immune pathways in the airway mucosa of 571 one‐month‐old asymptomatic neonates from the Copenhagen Prospective Studies on Asthma in Childhood2010 birth cohort (COPSAC2010 ). The association between airway mediator levels and presence of siblings was investigated using conventional statistics and principle component analysis (PCA). Results: Neonates with siblings had an upregulated level of airway immune mediators, with predominance of Type 1‐ and Type 17‐related mediators. This was supported by the PCA showing a highly significant difference between children with vs without siblings: P < 10 −10, which persisted after adjustment for potential confounders including pathogenic airway bacteria and viruses: P < 0.0001. The immune priming effect was inversely associated with time since last childbirth: P = 0.0015. Conclusions: Siblings mediate a Type 1/Type 17‐related immune‐stimulatory effect in the airways of asymptomatic neonates, also after adjustment for pathogenic bacteria and viruses, indicating that siblings exert a transferable early immune modulatory effect. These findings may represent an in utero immune priming effect of the fetal immune system caused by previous pregnancies as the effect was attenuated with time since last childbirth, or it could relate to the presence of unidentified microbes, but further studies are needed to confirm our findings.